스퍼터링을 통하여 다공성 양극산화 알루미늄 기판에 증착되는 니켈 박막의 기공 크기 조절 - 지상훈(Sanghoon Ji); 장춘만(Choon-man Jang); 정우철(Woochul Jung) (한국수소 및 신에너지학회 논문집, 2018)
The pore size of nickel (Ni) bottom electrode layer (BEL) for low-temperature solid oxide fuel cells embedded with ultrathin-film electrolyte was controlled by changing the substrate surface morphology and deposition process parameters. For ~150-nm-thick Ni BEL, the upper side of an anodic aluminum oxide (AAO) substrate with ~65-nm-sized pores provided ~1.7 times smaller pore size than the lower side of the AAO substrate. For ~100-nm-thick Ni BEL, the AAO substrate with ~45-nm-sized pores provided ~2.6 times smaller pore size than the AAO substrate with ~95-nm-sized pores, and the deposition pressure of ~4 mTorr provided ~1.3 times smaller pore size than that of ~48 mTorr. On the AAO substrate with ~65-nm-sized pores, the Ni BEL deposited for 400 seconds had ~2 times smaller pore size than the Ni BEL deposited for 100 seconds.